2005
DOI: 10.1175/jas3614.1
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Balance Analysis of Deep Convective Self-Aggregation above Uniform SST

Abstract: The spatial organization of deep moist convection in radiative-convective equilibrium over a constant sea surface temperature is studied. A 100-day simulation is performed with a three-dimensional cloud-resolving model over a (576 km) 2 domain with no ambient rotation and no mean wind. The convection self-aggregates within 10 days into quasi-stationary mesoscale patches of dry, subsiding and moist, rainy air columns. The patches ultimately merge into a single intensely convecting moist patch surrounded by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

94
945
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 485 publications
(1,045 citation statements)
references
References 20 publications
(27 reference statements)
94
945
6
Order By: Relevance
“…One clear sign of convective aggregation is an abnormally dry mean atmospheric state ( 20% RH between 2 and 10 km in Bretherton et al [2005] (Figure 4a, Tobin et al, 2012). This behavior is not pronounced in the present simulations (Figure 5), rather the relative humidity profiles are comparable to the tropical mean profiles of comprehensive GCM simulations.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016mssupporting
confidence: 43%
See 2 more Smart Citations
“…One clear sign of convective aggregation is an abnormally dry mean atmospheric state ( 20% RH between 2 and 10 km in Bretherton et al [2005] (Figure 4a, Tobin et al, 2012). This behavior is not pronounced in the present simulations (Figure 5), rather the relative humidity profiles are comparable to the tropical mean profiles of comprehensive GCM simulations.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016mssupporting
confidence: 43%
“…Specific limitations of modeled clouds include both features which differ from what one observes (e.g., ''too few, too bright,'' [Webb et al, 2001;Nam et al, 2012]) as well as features which are inadequately understood (e.g., controls on cloud vertical structure [Nuijens et al, 2015], and organization [Bretherton et al, 2005;Muller and Held, 2012;Wing and Emanuel, 2014]). An important component of these limitations is the delicacy of the interactions between clouds and circulations Sherwood et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for more than 20 years, however, that convection in numerical model simulations of radiative-convective equilibrium frequently gathers itself together, increasing in spatial scale until, under many circumstances, the entire domain contains only a single region of convection (Held et al 1993;Bretherton et al 2005;Stephens et al 2008;Wing and Emanuel 2014;Tompkins and Craig 1998). The phenomenon of convective 'self-aggregation' was originally noted in cloud-resolving models in which deep convection is explicit (Held et al 1993;Bretherton et al 2005;Stephens et al 2008;Wing and Emanuel 2014) but it also appears in global models (Bony et al 2016;Shi and Bretherton 2014;Reed et al 2015;Coppin and Bony 2015) in which convection is parameterized.…”
mentioning
confidence: 99%
“…Many studies have found a strong relationship between tropospheric water vapour and precipitation in observations (Bretherton et al, 2004;Peters and Neelin, 2006;Holloway and Neelin, 2009) and CSRMs (Grabowski, 2003;Derbyshire et al, 2004;Bretherton et al, 2005). However, parametrized convection usually lacks this strong relationship; in particular, models with parametrized convection tend to have too much light rain falling in relatively dry tropospheric conditions (Thayer-Calder and Randall, 2009, their figure 4).…”
Section: Environmental Conditions By Rain Ratementioning
confidence: 99%